A one year review of various complications in fracture shaft of femur managed with closed intramedullary interlocking nail - Afsar, Sardar Sohail; Gulzar, Mohammad; Babar, Iqtidar Ullah (Journal of Postgraduate Medical Institute, 2013)
Objective: To determine the frequency of complications in fractures shaft of femur managed by close antegradeintramedullary interlocking nail. Methodology: It was a descriptive cross sectional study of one year duration from March 2010 to March2011 held at department of Orthopedics and Traumatology, Lady Reading Hospital Peshawar. Forty fourconsecutive patients with femoral shaft fracture fulfilling the inclusion criteria were managed with closedantegrade interlocking nail. Complications in terms of infection, angulation, rotation, non-union, shorteningand knee stiffness were measured. Results: The mean age of the patients was 33.70+14.53 years. Twelve patients (27.3%) were females and32(72.2%) were males. Thirty five (79.5%) had road traffic accident, 3 (6.8%) sustained fractures due tofall from a height and 6 (13.6%) were due to fire arm/bomb blast injury. Thirty five (79.5%) had closeand 9(20.5%) had open fracture. There were four cases (9.1%) of infection; (two superficial and two deepwound infection). 40 patients (90.9%) regained full range of motion (00 - >1300) in knee and 4 patients(9.1%) had 00-1200 range of motion. There was only one case (2.3%) of up to 2.5cm limb shortening.42(95.4%) patients achieved union. Two (4.5%) patients had non-union. These patients were treated bystandard protocol of exchange nailing after reaming and ultimately achieved union. Three cases (6.8%)had angulation of > 100 (dorsal or ventral). None of our patients in this study had rotation deformity. Conclusion: Most common early complication with closed antegrade intramedullary nailing was infectionand late complication was non-union.